Study on Coping Strategies on Menopausal Symptoms on Middle Aged Women in Chattogram City (Journal of Chittagong Medical College Teachers' Association, 2026)
Background: Menopause is a physiological change in the life of women. Menopausal women require more information about their physical and psychosocial needs.  Most interventions for menopause women have focused on educational intervention, physical activity/exercise, healthy diet, stress management. The objectives of the study were to determine the commonly reported menopausal symptoms among middle age women and to correlate identified menopausal problems with coping strategies found in participants.   Materials and methods: The cross-sectional  observational study was conducted in Chattogram for One  year (January 2021 to December 2021).  Study population was women of 40 to 60 years who had given consent to participate in this study. They were residing in Chattogram metropolitan city. Using purposive sampling technique, a total number of 109 subjects were included. This study is conducted by using modified MRS questionnaire, to document of 12 symptoms (Divided into somatic, psychological and urogenital domain) commonly associated with menopause. The respondents were divided into two groups, case 59 and control 50. Results: The findings of the study are 84.7% (50) of the respondents are 45-50 years range and15.3% in the age range of 51-60 years in case. The study found that most of the women around 89% are suffering from depression, anxiety, 75% of the study population has joint paint and weakness and lack of confidence about self-wellbeing. 9% presented with hot flashes, 47% with sleep disturbances and 72 % presented with comorbidities. 80% of the respondent expressed their satisfaction in communication with friends and relatives, having rest and taking light exercise like walking, etc. Change in life style, diet and social adjustment in post intervention testing. It indicated that menopausal syndrome of participants was significantly improved in the intervention group compared to the control group (p < 0.001).    Conclusion:  Proper knowledge and empowerment of menopausal women will guarantee their health. It will also help them to overcome the barriers in health promotion and empowerment.JCMCTA 2025 ; 36 (2) : 161-164